Evaluation of the roughness, color match, and color stability of two monochromatic composite resins: a randomized controlled laboratory study - Iara Campos Santana; Sabrina Sobral de Oliveira; Karolina Pena Botelho; Renan Leonardi de Oliveira Rigotti; José Cristiano Ramos Glória; Adriana Maria Botelho; Dhelfeson Willya Douglas-de-Oliveira; Karine Taís Aguiar Tavano (BMC Oral Health)
Abstract Objective To assess the efficacy of monochromatic resins in capturing adjacent tooth color across various shades and cavity types, both before and after thermocycling. Furthermore, the surface roughness of the restorations was evaluated. Methodology This is a laboratory test that used 40 mandibular incisors with a healthy crown obtained from the Human Teeth Bank of the UFVJM School of Dentistry. The teeth were randomly assigned to two groups: one group was restored with Omnichroma composite resin, while the other one was restored with Vittra APS Unique composite resin. Three preparations were performed on each tooth in both groups, namely: Classes III, IV and V. Evaluations of USPHS and modified FDI criteria, analysis of roughness using a using a digital surface roughness tester and color reading with a spectrophotometer before and after thermocycling were performed. The data were submitted to descriptive statistics, Chi-square test and the T-test using the SPSS software, and a p-value of < 0.05 was considered statistically significant. Results There was no significant difference between the groups in relation to the parameters of shape (p > 0.05), marginal integrity (p > 0.05) and color (p > 0.05) in the USPHS analysis, as well as the ΔE in the CIEL* a* b* analysis (p > 0.05) and color in the FDI analysis (p > 0.05), in all classes. Clinically detectable differences were observed between classes IV (ΔE = 3.80) and V (ΔE = 5.02) restorations of the Omnichroma resin compared to the tooth. The ∆E of Vittra resin was considered unacceptable in all classes (ΔE varied from 4.35 to 5.52). The Vittra resin class III restoration showed the best adaptability (L*: p = 0.462; a*: p = 0.252 and b*: p = 0.335). There was no statistically difference between groups in the surface roughness analysis either initially (p = 0.564) or after thermocycling (p = 0.690). Conclusions It was concluded that the color match of the composite resins Omnichroma and Vittra APS Unique was found to be clinically satisfactory in USPHS and FDI analysis. Both resins showed low surface roughness.